Implementación de una infraestructura de red con tecnología Gigabit Ethernet, e IEEE 802.1 1N, y configuración de servicios para la intranet de la empresa Begoro S.A. en la ciudad de Santa Rosa provincia de El Oro en el año 2011 - Sigüenza Dávila, Walter Wagner (2013)
This project which is detailed below, was made in the company Begoro SA in the city of Santa Rosa, a leading carbonated drinks companies that is present throughout the province of El Oro and is currently expanding level international and international north of Perú.